2009
DOI: 10.1111/j.1472-765x.2008.02504.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular protectants produced byClostridium perfringenscells at elevated temperatures

Abstract: Aim:  The mechanisms of adaptation of Clostridium perfringens to high temperatures are not well understood. In this work, the involvement of extracellular compounds in protection to heat was determined. Methods and Results:  Cells were grown in fluid thioglycollate medium or chicken broth. When mid‐log phase was reached, they were heat‐shocked at 50°C for 30 min. Then cultures were centrifuged and supernatants were transferred to nonshocked cells. Heat tolerance of these cells was performed at 55°C. Viable cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…This observation suggests that the presence of specific proteins somehow alerts or protects the non pre-stressed cells leading to an increased thermotolerance. These findings are in agreement with the conclusion of Heredia et al (2009), who studied the involvement of extracellular compounds in the protection of Clostridium perfringens to heat, and showed that extracellular factors (proteins) produced by heat shocked cells have a thermoprotective function for non-stressed cells.…”
Section: Discussionsupporting
confidence: 92%
“…This observation suggests that the presence of specific proteins somehow alerts or protects the non pre-stressed cells leading to an increased thermotolerance. These findings are in agreement with the conclusion of Heredia et al (2009), who studied the involvement of extracellular compounds in the protection of Clostridium perfringens to heat, and showed that extracellular factors (proteins) produced by heat shocked cells have a thermoprotective function for non-stressed cells.…”
Section: Discussionsupporting
confidence: 92%
“…The implications of these findings are extremely critical. Recently, it has been demonstrated that production of exometabolites of C. perfringens during heat challenge plays an important role in heat tolerance of this bacteria (Heredia et al 2008).…”
Section: Growth In Food Prevention and Controlmentioning
confidence: 99%
“…The depleted content of divalent cations of endospores (such as in an adverse pH environment) would cause the decrease of their heat resistance, while the demineralized endospores would regain the heat resistance (Bender and Marquis ), but Yamazaki and others () found that the changes of heat resistance of A. acidoterrestris endospores were not significant when different divalent cations (including Ca 2+ ) were added into the medium, with better effects being observed when DPA and Ca 2+ were both added. Other factors influencing the heat resistance of vegetative cells include cell age, which is reflected in that the heat resistance is usually lower during the logarithmic phase than during the stationary phase, and cell populations, with large cell populations always to increase the heat resistance by excreting thermoprotective, extracellular proteins (Heredia and others ).…”
Section: General Characteristics Of Alicyclobacillusmentioning
confidence: 99%